Hear My Cry: Breaking the Code of Silence around Intimate Partner Violence among Black Women in and beyond Midlife - Waldron, Ingrid; MacDougall, Eileigh Storey; Weeks, Lori E. (Atlantis, 2021)
There is a knowledge gap about how the intersections of gender, race, culture, age, income, social class, and other identities shape Black women’s experiences of intimate partner violence (IPV). In this qualitative study, we utilized an intersectional approach to examine how IPV is experienced and managed by racialized women, and in particular, our focus was to explore the IPV experiences of Black Nova Scotian women in and beyond midlife and their experiences of seeking support. Participant recruitment was predictably challenging, but we were able to collect in-depth interview data from a Black woman who identified as being in and beyond midlife and who had experienced IPV in the past and from three people who provided support to Black women in a paid capacity. An interpretive narrative approach was utilized to identify five dominant themes: descriptions of the experiences of IPV for Black women; strategies for coping with IPV; strategies in supporting Black women experiencing IPV; barriers in accessing support; and challenges in the delivery of support. The knowledge gained through this research provides important insights about the experiences, barriers faced, and how to address these challenges for Black women who experience IPV in and beyond midlife.